Gênero, corpo e beleza no discurso publicitário : uma análise semiolinguística de anúncios direcionados à mulher - Viegas, Paula Rickes (2017)
Seeking to recognize the discursive strategies that are being used in advertisements aimed at women, the present study proposes to perform a semiolinguistic analysis, with the intention of reflecting about persuasive advertising and its gender marks. Advertising is recognized as an instance of production, responsible for the possible effects of meaning, which operates by economic, technological and symbolic logics. The cutting of the object to be analyzed was made in order to cover popular aspects of Brazilian consumption. And for this reason the choice fell on television and the fashion retail, as a means and segment to be observed. The ads were collected on TV Globo in March 2016 through a search for ads that targeted women. It was then that the fashion segment - represented by the stores Marisa, Renner and Riachuelo - stood out and appropriated significant speeches in relation to the objective of this study. The research is structured in two theoretical chapters, one about the advertising discourse through a theoretical-methodological approach and another about the gender. In this second chapter, concepts such as gender performativity, the subjectivity of the body and myth of beauty are approached. Always aiming to reflect on the analyzed object. In the third chapter, three commercial ads are analyzed through the semi-linguistic method - which considers three levels, proposed by Charaudeau: situational, communicational and discursive. Finally, the condition of "contrastiveness" is recognized, pointing out differences and constants in the ads analyzed, collaborating to interpret the results of the analysis. It can be noticed that, even trying to break with certain traditional discourses about women, advertising still can not dissociate itself from old and traditional discursive strategies in the seduction and persuasion of this public, especially in the case of television.